2022
DOI: 10.1093/plphys/kiac434
|View full text |Cite
|
Sign up to set email alerts
|

Tonoplast-localized transporter ZmNRAMP2 confers root-to-shoot translocation of manganese in maize

Abstract: Almost all living organisms require manganese (Mn) as an essential trace element for survival. To maintain an irreplaceable role in the oxygen-evolving complex of photosynthesis, plants require efficient Mn uptake in roots and delivery to above-ground tissues. However, the underlying mechanisms of root-to-shoot Mn translocation remain unclear. Here, we identified an Natural Resistance Associated Macrophage Protein (NRAMP) family member in maize (Zea mays), ZmNRAMP2, which localized to the tonoplast in maize pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Quantitative analysis revealed that ZmHMA3 had h expression in B73 roots than in Mo17 (Figure 2A). ZmHMA3 was upregulated in root stems under Cd stress, and this result is similar to previous studies on OsHMA2, AtHM and HvHMA2 [33]. These genes are involved in transporting metals from the subsu…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Quantitative analysis revealed that ZmHMA3 had h expression in B73 roots than in Mo17 (Figure 2A). ZmHMA3 was upregulated in root stems under Cd stress, and this result is similar to previous studies on OsHMA2, AtHM and HvHMA2 [33]. These genes are involved in transporting metals from the subsu…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative analysis revealed that ZmHMA3 had higher expression in B73 roots than in Mo17 (Figure 2A). ZmHMA3 was upregulated in roots and stems under Cd stress, and this result is similar to previous studies on OsHMA2, AtHMA2, and HvHMA2 [33]. These genes are involved in transporting metals from the subsurface to the above ground, and they have various functions in transporting metals into or out of cells and in loading or unloading metals in the xylem [33,34].…”
Section: Discussionsupporting
confidence: 89%
“…AtNRAMP6 is localized in the plasma membrane and intima, including the endoplasmic reticulum [70]. OsNRAMP2 and ZmNRAMP2 are tonoplast-localized transporters [71,72]. In this study, The MsNRAMP2 protein is located in the whole cell, including the nucleus and cytoplasm but not in the chloroplast (Figure 4).…”
Section: Discussionmentioning
confidence: 61%
“…To date, orthologous proteins of AtNRAMP1 have been characterized in various species, such as rice and corn. They are play essential roles in the tolerance to the Mn deficiency condition (Sasaki et al 2012;Ueno et al 2015;Guo et al 2022). Previous research has shown that TpN-RAMP3 in dwarf Polish Wheat (Triticum polonicum L) possesses Mn, Cd, and Co transport activities, and improve tolerance to Mn toxicity in Arabidopsis (Peng et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, OsNRAMP5 is located at the far end of the outer and endodermis cells, and is the main transporter of Mn and Cd, responsible for transporting Mn and Cd from the external solution to the root cells (Sasaki et al 2012;Ueno et al 2015). Recent studies have reported that ZmNRAMP2 in maize is located on tonoplast to mediate Mn transport (Guo et al 2022).…”
Section: Introductionmentioning
confidence: 99%